2021
DOI: 10.1177/13684302211052511
|View full text |Cite
|
Sign up to set email alerts
|

Personal narratives to improve attitudes towards stigmatized immigrants: A parallel-serial mediation model

Abstract: This work addresses the study of factors that increase the persuasive efficacy of testimonial messages aimed at improving intergroup attitudes. The results of two online experiments ( N = 840) on the effect of empathy with, and similarity to, the protagonist in personal stories designed to improve attitudes towards immigrants are presented. In both studies, participants were given instructions to induce a certain exposure condition (empathy vs. an objective or distanced perspective) immediately before reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
1
4
0
1
Order By: Relevance
“…This model suggests that through cooperation, interaction, facing common problems, and emphasizing common destiny, two separate group representations can be transformed into a broader supergroup, i.e., recategorization into a common ingroup identity, which can reduce negative stereotypes and prejudices between the two groups [ 29 ]. Similarity increased identification and narrative transportation, which in turn reduced counterarguing, thus resulting in a more positive attitude towards the outgroup [ 30 ]. The use of comics to portray doctors as hard workers serve to challenge these stereotypes and reduce stigma.…”
Section: Discussionmentioning
confidence: 99%
“…This model suggests that through cooperation, interaction, facing common problems, and emphasizing common destiny, two separate group representations can be transformed into a broader supergroup, i.e., recategorization into a common ingroup identity, which can reduce negative stereotypes and prejudices between the two groups [ 29 ]. Similarity increased identification and narrative transportation, which in turn reduced counterarguing, thus resulting in a more positive attitude towards the outgroup [ 30 ]. The use of comics to portray doctors as hard workers serve to challenge these stereotypes and reduce stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we acknowledged that Twitter could also serve as an optimal platform for sharing testimonial messages for raising awareness around prevention measures during the pandemic. We consider that testimonial messages disseminated through social networks such as Twitter could constitute narrative vaccines [ 49 , 65 ] or narrative pills [ 66 ] that spread personal stories that facilitated a persuasive impact, especially among the younger population. In our case, the testimonial message was led by a young person who narrated a risky behavior (holding a party without taking COVID-19 prevention measures) that resulted in a COVID-19 infection that affected either the young person or a family member with whom they lived (contagion target).…”
Section: Discussionmentioning
confidence: 99%
“…In two separate studies, Johnson (2013) also found vicarious outgroup contact with Muslims through narrative fiction bolstered empathy and reduced prejudice toward Arab Muslims via transportation into the fictional story. Similarly, Igartua and Cachón-Ramón (2021) found as narrative transportation increased with immigrant testimonials, counterarguing was reduced, resulting in more positive attitudes toward the outgroup.…”
Section: Integrated Mediated Intergroup Contact Modelmentioning
confidence: 94%